2016
DOI: 10.1155/2016/1469590
|View full text |Cite
|
Sign up to set email alerts
|

Does Citrulline Have Protective Effects on Liver Injury in Septic Rats?

Abstract: Citrulline (Cit) supplementation was proposed to serve as a therapeutic intervention to restore arginine (Arg) concentrations and improve related functions in sepsis. This study explored whether citrulline had positive effects on liver injury and cytokine release in the early stages of sepsis. The cecal ligation and puncture (CLP) model was utilized in our study. Rats were divided into four groups: normal, Cit, CLP, and CLP+Cit. The CLP group and CLP+Cit group were separated into 6-, 12-, and 24-hour groups, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
17
0
2
Order By: Relevance
“…Thus, platelet count reduction can be used as an effective early warning index of the severity and prognosis of septic patients. We found that, in a previous study, exogenous Cit alleviated the release of proinflammatory cytokines (TNF- α , IL-1 β , and IL-6) in early sepsis and increased the release of late-stage anti-inflammatory cytokines (IL-4 and IL-10) to alleviate the inflammatory response of septic rats [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, platelet count reduction can be used as an effective early warning index of the severity and prognosis of septic patients. We found that, in a previous study, exogenous Cit alleviated the release of proinflammatory cytokines (TNF- α , IL-1 β , and IL-6) in early sepsis and increased the release of late-stage anti-inflammatory cytokines (IL-4 and IL-10) to alleviate the inflammatory response of septic rats [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the main reasons for organ damage caused by sepsis include inflammatory cytokines and oxidative stress injury. An increase in cardiomyocyte apoptosis can increase iNOS and NADPH oxidase expression as well as NO and superoxide production, thereby inducing oxidative stress and other damage [ 4 6 ]. Antioxidant enzymes are commonly assessed to determine the extent of cell damage after an oxidative stress response.…”
Section: Introductionmentioning
confidence: 99%
“…The greatest challenge is to mimick the clinical complexity of human sepsis and test possible therapeutic targets. The CLP method, the most widely used in scientific research, is considered the gold standard (Ercan and Ozdemir, 2015;Cai et al, 2016). In this study, the CLP model was used in rats to investigate the anti-inflammatory effects of Hev b 13 during sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…These initiate an immunological cascade resulting in the release of pro-inflammatory interleukins, including the tumor necrosis factor (TNF-α), interleukin (IL) 1, IL-2, IL-6, IL-8, and IL-12, among others (Cai et al, 2016). Overproduction of these inflammatory mediators (cytokine storm) induces vasodilation, increased capillary permeability, hypotension, hemoconcentration, macromolecular leakage and edema, and may lead to multiple organ dysfunction syndrome (MODS), where the lungs are the most frequently affected (Matsuda and Hattori, 2006;Stearns-Kurosawa et al, 2011;Ates et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Метааналіз 341 пацієнта продемонстрував, що в пацієнтів із септичним станом концентрація аргініну плазми була на 41 % менше, ніж у контрольній групі. Однак клінічні рандомізовані дослідження показали, що вживання аргініну не сприяє достовірному зменшенню госпітальної смертності та інфекційних ускладнень [17].…”
Section: вступunclassified